2013
DOI: 10.1183/09031936.00181312
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cell motility in pulmonary arterial hypertension

Abstract: Pulmonary artery smooth muscle cells (PASMC), in pulmonary arterial hypertension (PAH), contribute to obliterative vascular remodelling and are characterised by enhanced proliferation, suppressed apoptosis and, a much less studied, increased migration potential. One of the major proteins that regulate cell migration is focal adhesion kinase (FAK), but its role in PAH is not fully understood. We hypothesised that targeting cell migration by FAK inhibition may be a new therapeutic strategy in PAH.In vivo, inhala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 67 publications
(76 reference statements)
4
33
1
Order By: Relevance
“…In PAH, the elevation of pulmonary arterial pressure is due to a combination of sustained vasoconstriction and structural remodeling, significant components of remodeling in PAH include medial thickening in muscularized pulmonary vessels, as well as extension of muscularization distally to small pulmonary arteries [33][34], both of which are associated with enhanced proliferation [35] and migration [36] of PASMCs. The sources of PASMCs may be proliferation or another type of cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In PAH, the elevation of pulmonary arterial pressure is due to a combination of sustained vasoconstriction and structural remodeling, significant components of remodeling in PAH include medial thickening in muscularized pulmonary vessels, as well as extension of muscularization distally to small pulmonary arteries [33][34], both of which are associated with enhanced proliferation [35] and migration [36] of PASMCs. The sources of PASMCs may be proliferation or another type of cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…PAH is a clinical condition associated with severe pulmonary vascular disorder due to excessive proliferation of pulmonary artery smooth muscle and endothelial cells, migration of pulmonary vascular smooth muscle cells 2 , remodelling of small pulmonary arteries with diminished apoptosis, enhanced inflammation and fibrosis in the lung tissue 3 . Vascular disorders result from complex interactions between oxidized lipoproteins, monocytes/macrophages, and injured endothelium and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…The article by PAULIN et al [6] focuses on FAK, a broadly expressed non-receptor kinase, which is a key participant in a range of cell functions, including cell adhesion, migration, proliferation and survival [17], contributing to angiogenesis, wound healing, cardiac hypertrophy and tissue fibrosis [18]. The current model for FAK signalling shows that FAK activation is triggered by integrin-dependent cell adhesion, by growth factor receptor activation or activation of G protein-coupled receptors [17].…”
mentioning
confidence: 99%
“…The current model for FAK signalling shows that FAK activation is triggered by integrin-dependent cell adhesion, by growth factor receptor activation or activation of G protein-coupled receptors [17]. Whereas UMAR et al [19] previously reported activation of FAK in the right ventricle of monocrotaline-induced pulmonary hypertensive rats [19], PAULIN et al [6] concentrated on pulmonary vascular remodelling and on a proofof-concept inhibition of FAK. Postulating that FAK may function as a signalling hub, they treated rats with established monocrotaline-induced pulmonary hypertension either with a single inhalation of FAK-small interfering RNA or oral treatment with a FAK inhibitor.…”
mentioning
confidence: 99%
See 1 more Smart Citation